Krajowy mechanizm prewencji – funkcje i zadania Rzecznika Praw Obywatelskich - Czerniawski, Ryszard (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The paper points out that the Commissioner for Civil Rights Protection of Poland performs the functions of a visiting body for the prevention of torture and other cruel, inhuman or degrading treatment or punishment (national preventive mechanism) as understood in the Optional Protocol to the Convention against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment, adopted by the General Assembly of the United Nations in New York on December 18, 2002.